G.B. PIRANESI'S ARTISTIC TRUTH ABOUT THE MODERNITY EPOCH - S. G. Gladysheva (Концепт: философия, религия, культура, 2017)
The article analyzes the culture of modernity as wholeness, perceived “through the prism” of G.B. Piranesi’s creative mind. It is emphasized, that being the creator of this wholeness, Piranesi is vital for his contemporaries and descendants. First of all, the modernistic character of the author’s self-evaluation and the specificity of Piranesian understanding of the artistic truth are stressed. The creative “self” of the artist is perceived as an autonomous center, the source of individual vision of reality; and at the same time being the result of free creative expression, claims to be its true “eidetic” vision. It is shown that such an understanding of the artist and the art was arising at the dawn of Modernity, starting from the Renaissance era. The genre of Capriccio is considered the quintessence of the method of creating the wholeness in human mind, and thus of disclosing the true nature of the represented reality. Its first philosophical analysis was initiated by V. Carducho, the painter and the art theorist, who lived at the turn of XVI - XVII centuries. He considered necessary to overcome copying of the nature and to open new ways, acting like the jumping mountain goat (lat. capra). G.B. Piranesi is represented as a master of the genre. A number of examples are considered: “Capricci”, “Grotesques”, etc., where he connects the unconnected, and thus expresses the idea of the whole. The idea of organizing Piranesian complete vision of the modern era on the same principle is put forward. The paper presents Piranesi’s self-consciousness as combining the characteristic features of Renaissance, Baroque, enlightenment worldviews. However, the assumption is made about the Baroque nature of connecting the elements into the wholeness. Particular “slices” of the Piranesi’s vision of his era are discussed. It is also shown that Piranesi was able to see and predict the negative consequences of the autonomous reason standpoint. The final evaluation is that Piranesi kept unchanged the modernity’s belief in the creative capacity of the individual “self” for the right eidetic holistic vision of reality.